PENGARUH PENGEMBANGAN KARIR DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN HOTEL CIPUTRA SEMARANG (Studi Kasus Karyawan Hotel Ciputra Semarang) - Kharismawati, Jessica Wahyu; Nugraha, Hari Susanta (Jurnal Ilmu Administrasi Bisnis, 2018)
Many new hotels in Semarang mark the increasingly intense competition in the hospitality industry. Hotel entrepreneurs are required to compete in attracting consumers, many ways that are done by doing promotions, discounts, advertising and so forth. One way that is used is to provide the best service for consumers. Hotel Ciputra as one of the renowned hotels in the city of Semarang always improve the quality of its service to satisfy the consumers. The emergence of five-star hotels such as Gumaya Tower Hotel, Crowne Plaza and Grand Candi Hotel, make Hotel Ciputra must do an evaluation to keep customers to be loyal. The problem of this research is that in 2014 the employee performance score of 80.0% there is decreasing performance in 2015 to 75,8% and in 2016 equal to 74,9%. The performance appraisal does not reach the 85% standard set by Hotel Ciputra. The purpose of this study is to determine the effect of career development and physical work environment on employee performance Hotel Ciputra Semarang. This type of research is Explanatory research. Sampling technique using Probability Sampling method. Probability Sampling is a sampling technique that provides equal opportunity for each element (member) of the population to be elected as a sample member. The number of samples taken as many as 111 respondents. Data were analyzed through validity test, reliability test, correlation coefficient, coefficient of determination, simple linear regression, multiple linear regression, T test, and F test with SPSS program aid. Based on the results of the analysis, showed that Career Development variables are in the strong category. Career Development has a positive effect on employee performance and contributed 36.9%. The Physical Work Environment is in the medium category. Physical Work Environment positively affects employee performance and contributes 30% to employee performance.